Deposição e caracterização de filmes ultrafinos de óxido de titânio depositados por Sputtering RF - Albuquerque, Diego Aparecido Carvalho (Universidade Federal de São Carlos, 2012)
This work studied ultrathin films of titanium oxide deposited by the technique r. f. reactive sputtering with different oxygen flows and different deposition times. Optical properties were studied (ultra-violeta/Visível) and the surface morphology (Atomic Force Microscopy). The composition and structural properties of the films were analyzed by X-ray diffraction and Rutherford Backscattering Spectroscopy. The films are amorphous and rough (fractal dimension around 2.6 to 2.7 and roughness around 1.6 to 2.5 nm). The stoichiometry was fairly close to the titanium dioxide (TiO2). The optical energy Gap obtained by three different models presented values between 3.0 to 3.5 eV.
Keywords: filmes ultrafinos; óxido de titânio; sputtering; thin films; titanium oxide; sputtering; óptical properties; afm; roughness; fractal dimension; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA